MANIPULASl POLA SADAP UNTUK MENINGKATKAN BASIL GETAH POHON AGATIS (AGATHIS SP.) - Ishak Sumantri; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1991)
Thia ptJPB preaenta  the  re1ult1 •of  invatifOtion   on tapping  design1 manipulation   to increae   relin• yield  of  A,aihiaap. cawied  out  in  Wono10bo  Sub  Fore1t  Diatrict,  Purworejo  Fore1t  District,   Unit 11 Perum  Perhutani  Central  Java, in 1989. The objective   iB  to  (ind  out  the  tapping  design  that  can increaae retin  yield.  For  thit  purpo•,    the 1lanted and horizontal tappi1111 daigna  were applied. Data   obtained   were  analysed   by  uaing neated  desilnl   with  2 x 6 'x 4 (acto1'1. The retult•are as foUowa :                                                                                                                                                                                                                                                                   I.  An  awrage  reain yie1d of  .Agathia ap. in  Wonoaobo  Sub  Foreat District was 2.4 7 gram/tree/day   with  the ro111e  between O. 71 and 8.29  gram/tree/day.2.  The Average  rain   y1Bld1  of  Alatbia   1p. uting 1lanted and horizontal  tapping  design1 were 2.80 and 2.66 gram/tree/day, re1Pectively.3.  The  average rain   yield•  of  Agathia 1p. in February,  .March, April,  .May and  June  were  1.88,  2.62,  2.62,  2.66 and 2.69 1n1m/tree/day,   rapectively.                                                                                                                               .4.  The  average  rain   yields  of  Agathia  1p. at  the  fir•t,  second,  third  and  fourth   tappings  were. 2.36,  2.46,  2.63  and  2.66 gram/tree/day,   respectively.5.  The  rain  yields among  tapping  months  were different   significantly   while the resin yields either  between  tappfn6  deligna or  amorw  tapping  (requencie1   were  not  Bignificantly  different.   Compered   to  relin  yield  of  horizontal   tappin6  de.Wn. the rain  yield  of 1lanted ta~ping deBign wa• 16% higher.